Ramadan Diurnal Intermittent Fasting Is Associated With Attenuated FTO Gene Expression in Subjects With Overweight and Obesity: A Prospective Cohort Study - Madkour, Mohamed I.; Malhab, Lara J. Bou; Abdel-Rahman, Wael M.; Abdelrahim, Dana N.; Saber-Ayad, Maha; Faris, MoezAlIslam E. (Frontiers in Nutrition, 2022)
Aim and Background: A growing body of evidence supports the impact of intermittent fasting (IF) on normalizing body weight and that the interaction between body genes and environmental factors shapes human susceptibility to developing obesity. FTO gene is one of these genes with metabolic effects related to energy metabolism and body fat deposition. This research examined the changes in FTO gene expression upon Ramadan intermittent fasting (RIF) in a group of metabolically healthy subjects with overweight and obesity. Methods: Sixty-three (63) subjects were recruited, of which 57 (17 males and 40 females, mean age 38.4±11.2 years) subjects with overweight and obesity (BMI=29.89±5.02 kg/ m2were recruited and monitored before and at the end of Ramadan month), and 6 healthy subjects with normal BMI (21.4 ± 2.20 kg/m2) recruited only to standardize the reference for normal levels of FTO gene expression. In the two-time points, anthropometric, biochemical, and dietary assessments were undertaken, and FTO gene expression tests were performed using RNA extracted from the whole blood sample. Results: Results showed that compared to normal BMI subjects, the relative gene expressions in overweight/obese were significantly decreased at the end of Ramadan (-32.30%, 95% CI -0.052 –0.981) in comparison with the pre-fasting state. Significant reductions were found in body weight, BMI, fat mass, body fat percent, hip circumference, LDL, IL-6, TNF-α (P<0.001), and in waist circumference (P<0.05), whilst HDL and IL-10 significantly increased (P<0.001) at the end of Ramadan in comparison with the pre-fasting levels. Binary logistic regression analysis for genetic expressions showed no significant association between high-energy intake, waist circumference, or obesity and FTO gene expression. Conclusions: RIF is associated with the downregulation of the FTO gene expression in subjects with obesity, and this may explain, at least in part, its favorable metabolic effects. Hence, RIF presumably may entail a protective impact against body weight gain and its adverse metabolic-related derangements in subjects with obesity.